Assessment of Serum Macrophage Migration Inhibitory Factor (MIF) as an Early Diagnostic Marker of Leptospirosis - Sumaiya, Krishnamoorthi; Akino Mercy, Charles Solomon; Muralitharan, Gangatharan; Hajinur Hirad, Abdurahman; Alarfaj, Abdullah A.; Natarajaseenivasan, Kalimuthusamy (Frontiers in Cellular and Infection Microbiology, 2022)
The search for valuable early diagnostic markers for leptospirosis is ongoing. The aim of the present study was to evaluate the diagnostic value of macrophage migration inhibitory factor (MIF) for leptospirosis. MIF is an immunoregulatory cytokine secreted by a variety of cell types involved in immune response and the pathogenesis of various diseases. It was previously described as a severity predictor of diseases. Samples of 142 leptospirosis cases, 101 other febrile cases, and 57 healthy controls were studied. The prevalence of leptospirosis was 47.3%. Autumnalis, Australis, and Canicola were the highly prevalent leptospiral serovars with a microscopic agglutination test (MAT) titer in the range 1:80–1:2,560. Enzyme-linked immunosorbent assay (ELISA) of MIF was carried out to measure the serum MIF levels. We found that the serum MIF levels [median, (interquartile range)] were significantly (p < 0.001) elevated in different clinical forms of leptospirosis, such as febrile illness [7.5 ng/ml (5.32–8.97)], pulmonary hemorrhage [13.2 ng/ml (11.77–16.72)], Weil’s syndrome [8.8 ng/ml (7.25–9.95)], and renal failure [8.6 ng/ml (7.18–10.5)], than in healthy controls [0.65n g/ml (0.5–1.1)]. Serum MIF had sensitivity, specificity, positive predictive value, and negative predictive value of 100%, >90%, >90%, and 100%, respectively. Receiver operating characteristic (ROC) analysis revealed that the serum MIF levels between leptospirosis cases and control subjects had an area under the curve (AUC) value of >0.9 (p < 0.0001). In leptospirosis patients, elevation of serum MIF was significantly (p < 0.001) higher in severe cases with organ dysfunction [10 ng/ml (7.8–14.5)] than that in mild febrile cases [7.5 ng/ml (5.32–8.97)], with the difference of 2.5 indicating that serum MIF acts as a predictor of leptospirosis severity. Pearson’s correlation test demonstrated that the serum MIF level was strongly correlated (r = 0.75, p < 0.0001) with disease progression. The median lethal dose (LD50) of leptospiral lipopolysaccharide (LPS) in BALB/c mice was determined to be 20 mg/kg, which gave rise to endotoxemia. Leptospiral LPS triggered the upregulation of MIF expression at 24 h post-infection, which reached the peak level at 24 h post-treatment in THP-1 cells and showed elevated MIF expressions in different tissues of BALB/c mice at the early stage of infection. Taken together, MIF is an early-phase cytokine that could serve as a rapid diagnostic marker for leptospirosis.